Grounding concepts an empirical basis for arithmetical knowledge - Jenkins, C. S. (Carrie S.); Oxford eBooks (Oxford : Oxford University Press, 2008)
Carrie Jenkins presents an account of arithmetical knowledge which manages to respect three key intuitions: a priorism mind-independence realism, and empiricism. Jenkins argues that arithmetic can be known through the examination of empirically grounded concepts, non-accidentally accurate representations of the mind-independent world.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Arithmetic -- Philosophy; Knowledge, Theory of; Electronic books